2011
DOI: 10.1128/mcb.06093-11
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Shuttling of Eukaryotic RNA Polymerase II

Abstract: The eukaryotic RNA polymerase II (RNAPII) transcribes most protein-coding RNAs (mRNAs) and the capped noncoding RNAs (ncRNAs), including microRNAs (miRNAs), small nuclear RNAs (snRNAs), and small nucleolar RNAs (snoRNAs) (10). In the past 3 decades, our knowledge about the functional role of RNAPII during gene transcription has dramatically advanced (8). However, there are still several open questions regarding the regulatory mechanisms involved in the steps before and after transcription. In particular, how R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…In light of the data presented in Figures 2 and 5 and in recent publications on the GPN proteins and the NLS-containing protein Iwr1 (Di Croce 2011), we propose a cooperative role for these proteins in RNAPII biogenesis and nuclear import. However, it is unclear whether the GPN proteins function primarily in assembly or nuclear import.…”
Section: Resultssupporting
confidence: 67%
“…In light of the data presented in Figures 2 and 5 and in recent publications on the GPN proteins and the NLS-containing protein Iwr1 (Di Croce 2011), we propose a cooperative role for these proteins in RNAPII biogenesis and nuclear import. However, it is unclear whether the GPN proteins function primarily in assembly or nuclear import.…”
Section: Resultssupporting
confidence: 67%
“…Multiple interactions between human Pol II and the small GTPase GPN1 indicated its involvement in Pol II assembly and nuclear import (12). Npa3, the yeast homolog of GPN1, is required for nuclear localization of yeast Pol II and binds it in a GTP-dependent manner (13), which argues that the mechanism involved in the subcellular localization of Pol II requires the catalytic function of GNP proteins and is conserved from yeast to mammals (14). Two other proteins involved in Pol II biogenesis, Iwr1 and Rtp1, were identified in genetic screens for suppressors of the growth defect caused by depletion of NC2, a negative regulator of mRNA transcription (15,16).…”
mentioning
confidence: 99%
“…Additionally, several proteins were identified that function together in large multi-protein complexes, including subunits of RNA polymerase II (RNAPII), transcription factor II D (TFIID) and Mediator complexes. The identification of RNAPII subunits is encouraging, as RNAPII is already suspected to assemble within the cytoplasm prior to nuclear import [ 42 , 43 , 69 ]. Similar to RNAPII, the assembly of TFIID subunits has been proposed to occur within the cytoplasm, and subsequently enter the nucleus through a piggybacking mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, several proteins represented within the group of cargo without predicted cNLSs are already known to use piggybacking, and these mainly belong to the RNAPII complex, where assembly has been shown to take place within the cytoplasm prior to nuclear import [ 43 , 69 ]. Additionally, several TAF proteins belonging to the TFIID complex were identified in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation